Estrategias para la introducción del Euro en la perspectiva de los países miembros de la comunidad europea - BaAkkrk, AGE F.P. (2020)
In this paper we analyse the economic policy challenges involved in the accession of the candidates to he European Union and, in particular, we assess appropriate exchange rate regimes both before and alter FU accession. In this sense. we conclude that generally the experience of accession countries shows that hey have been capable of mamtaming the line balance between price stability and confidence in their currency, adapting the exchange rate regime If needed. Ás such. the trade-o11 between fixed and Mexible regimes lies both in the changing challenges ofa maturing transition economy and the structural strength and flexibility of the domestic market. Neither regime can be a panacea in itself, but to exclude the option oFPexchange rate adjustment prematurely could be a mistake.